DETERMINATION OF HEN EGGSHELL STRENGTH BY THE PUNCTURE METHOD - Koprivica, Ranko; Veljkovic, Biljana (Journal on Processing and Energy in Agriculture, 2021)
The aim of this study was to design and apply the measuring acquisition system, or a device for determining the limit values of eggshell strength using the puncture method. This study focused on class "M" eggs produced on a laying hen farm in the vicinity of Čаčak, and determined the external physical properties of egg quality: length, width, shape index and weight. In addition, the following eggshell properties were determined: weight, proportion, thickness, and puncture force. Average egg length was 58.05 mm, width 45.46 mm, and shape index 78.25. Average egg weight was 65.89 g, and the eggshell ratio 12.76% (8.44 g). Average eggshell thickness was 0.48 mm with a 4.69% coefficient of variation. Results showed that the tested eggs had uniform strength, with average value of the minimum shell puncture force 26.34 N, with a 0.95% coefficient of variation.